Periangular transmasseteric infraparotid approach in the treatment of condylar-base and low condylar‐neck fractures - Hirjak, Dušan; Vavro, Michal; Dvoranová, Bronislava; Gális, Branislav; Šimko, Kristián; Malíček, Ľubomír; Machoň, Vladimír; Neff, A (Bratislavské lekárske listy, 2021)
AIM: Mandibular condylar fractures account for 25 to 52 % of all mandibular fractures. Though current literature favors open reduction and internal fixation (ORIF) of condylar‐base and low condylar‐neck fractures, extraoral approaches are usually considered to be complicated by the risk of facial nerve injury and other possible complications. This study was undertaken to demonstrate that the periangular transmasseteric infraparotid surgical approach (TMIP) to condylar‐base and low condylar‐neck fractures provides excellent access to the bony fragments with minimal risk of complications such as facial nerve and parotid gland injury. PATIENTS: In the period from January 2010 to December 2018, 81patients (96 fractures) with condylar‐base and low condylar‐neck fractures underwent ORIF via periangular transmasseteric infraparotid surgical approach. RESULTS: The results of this retrospective study showed minimal postoperative complications. The periangular transmasseteric infraparotid surgical approach allowed precise anatomic repositioning and fixation of the bony fragments in almost all cases except for two juvenile cases with noticeable scars and one case with plate fracture. There were no transient or permanent facial nerve palsies, parotid gland or salivary fistulae complications during a 12‐month follow‐up period. CONCLUSION: The periangular infraparotid transmasseteric approach to ORIF of condylar‐base and low condylar‐neck fractures is an effective and safe approach allowing accurate anatomic reposition and fixation of the fragments with minimum surgical complications (Tab. 1, Fig. 12, Ref. 21).
Keywords: dospělí; Mandibular Fractures; Facial Nerve Injuries; fraktury mandibuly; Humans; lidé středního věku; parotis; Middle Aged; Young Adult; fixace fraktury; mladý dospělý; mužské pohlaví; poranění nervus facialis; Adult; Adolescent; Parotid Gland; ženské pohlaví; lidé; mladiství; Aged; senioři; Male; Fracture Fixation; Female